2001
DOI: 10.1515/jpm.2001.047
|View full text |Cite
|
Sign up to set email alerts
|

Patent ductus arteriosus in very low birthweight infants: complications of pharmacological and surgical treatment

Abstract: Despite the short-comings inherent to retrospective analyses, we propose that surgery should be reserved for infants not responding to pharmacological PDA closure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
0
6

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(84 citation statements)
references
References 27 publications
1
77
0
6
Order By: Relevance
“…The rate of ligation in the present study, in infants receiving more than one course of indomethacin, although higher than reported in recent cohort studies (6,8,(10)(11)(12), was still within the range reported in the literature (4,5,15,17,18). Koehne et al (4) reported an overall ligation rate of 57% and a 34% ligation rate in 101 babies who had indomethacin treatment.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The rate of ligation in the present study, in infants receiving more than one course of indomethacin, although higher than reported in recent cohort studies (6,8,(10)(11)(12), was still within the range reported in the literature (4,5,15,17,18). Koehne et al (4) reported an overall ligation rate of 57% and a 34% ligation rate in 101 babies who had indomethacin treatment.…”
Section: Discussionsupporting
confidence: 60%
“…Koehne et al (4) reported an overall ligation rate of 57% and a 34% ligation rate in 101 babies who had indomethacin treatment. This cohort, comprised of patients treated between 1987 and 1998, was not restricted to infants <27 weeks' gestation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9,12 Finally, indomethacin usage is not without potential adverse side effects. 13 Therefore, it is necessary to better characterize and define the ELBW population at-risk for developing an sPDA rather than to treat all ELBW neonates indiscriminately. To accomplish this, it is essential to develop a method that will accurately predict which ELBW neonates, if any, might benefit from early intervention.…”
Section: Introductionmentioning
confidence: 99%